The ACP secretariat calls for withdrawal of the challenge to the EU sugar regime - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The ACP secretary-general issued a statement on October 22nd 2002...